RESPONSES OF IONOSPHERE OVER BANDUNG AND PONTIANAK TO THE CME EVENTS DURING THE 24th SOLAR MAXIMUM CYCLE (2012-2015) - BERNOULLY SAILENDRA JEFONS (NIM: 20315305), NEWTON
Sun is the main source of space weather dynamic trigger. Solar activities take control to keep the environment of the Solar system. Some Solar activity are Sun spots, flare events, coronal holes and coronal mass ejection (CME). These activities are connected one another and sometime could occur simultaneously. CME is one of the Solar activities caused by the mass of the Sun ejected out from the corona to the interplanetary space. And not only that sometime CME could disturb the environment of the Earth. On of the disturbance caused by CME is the anomaly of F2 layer on EarthÃ‚Â’s ionosphere. In this research, the analysis about ionospheric responses to the CME events during the 24th Solar maximum cycle (2012-2015) had been done and obtained 35 CME's potentially causing the anomaly on the ionosphere. The analysis result shows that the delay time of CME's event for two places (stations) at different latitude are 35.9 hours for near Earth's geomagnetic equatorial latitude (Pontianak station) and 27.12 hours for near pole latitude (Tanjung Sari station). It can be concluded that the region above Tanjung Sari is more sensitive than the region above Pontianak, marked by the significant decreasing of foF2 values at Tanjung Sari.